2012
DOI: 10.1001/archneurol.2011.3367
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the D620N Mutation in VPS35 in Parkinson Disease

Abstract: Objective: To evaluate the frequency and clinical spectrum of the recently identified p.D620N mutation in the VPS35 gene in Parkinson disease (PD) in an international sample. Design: Genetic analysis by DNA sequencing and detailed clinical and neuropsychiatric assessment as well as neuroimaging in mutation carriers. Setting: Tertiary referral centers in Germany, Serbia, Chile, and the United States. Patients: One thousand seven hundred seventy-four patients with PD. Main Outcome Measure: Frequency of the p.D62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 14 publications
1
62
1
Order By: Relevance
“…Recently, the p.D620N mutation in the VPS35 gene was identified as a novel cause of autosomal dominant lateonset PD by two research groups [212,213] and five subsequent studies have identified this mutation in PD patients [214][215][216][217]. Moreover, PD-associated defects in RAB7L1 or LRRK2 lead to a deficiency of the VPS35 component of the retromer complex [218].…”
Section: Vps35 (Park17)mentioning
confidence: 99%
“…Recently, the p.D620N mutation in the VPS35 gene was identified as a novel cause of autosomal dominant lateonset PD by two research groups [212,213] and five subsequent studies have identified this mutation in PD patients [214][215][216][217]. Moreover, PD-associated defects in RAB7L1 or LRRK2 lead to a deficiency of the VPS35 component of the retromer complex [218].…”
Section: Vps35 (Park17)mentioning
confidence: 99%
“…Depression seemed to be more common than cognitive impairment. Atypical motor features were not found [12][13][14][15][16][17][18].…”
Section: Clinical Presentationmentioning
confidence: 87%
“…Exciting new studies implicate the VPS35 retromer subunit and the retromer complex in PD and mitochondrial fission, forging a novel connection between an endocytic regulatory complex and a non-endocytic organelle (Follett et al, 2014;Kumar et al, 2012;Sharma et al, 2012;Struhal et al, 2014;Tang et al, 2015;Vilarino-Guell et al, 2011;Zimprich et al, 2011). However, while the relationship between VPS35, mitochondrial dynamics and PD is now irrefutable, the precise mechanism(s) by which VPS35 influences mitochondrial morphology remain somewhat controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified an important role for the retromer cargo selection complex protein VPS35 in the regulation of mitochondrial homeostasis and PD (Kumar et al, 2012;Struhal et al, 2014;Vilarino-Guell et al, 2011;Wang et al, 2016a,b;Zimprich et al, 2011). One recently published mechanism suggests that VPS35 controls the transport of the ubiquitin ligase Mul1 to the mitochondrial membrane (Tang et al, 2015).…”
Section: Ehd1 and Rabankyrin-5 Regulate Retromer Control Of Mitochondmentioning
confidence: 99%
See 1 more Smart Citation